Measuring Palatal Height in Normal Occlusion and Malocclusions - M. Zarringhalam (Tehran University of Medical Sciences, 2004)
Statement of Problem: Due to the appearance of palatal height difference in orthodontic patients we decided to carry out this study. Purpose: The purpose of this research was to determine palatal height in persons with normal occlusion and different malocclusions (class I, II Div I and III) and comparing them with each other. Materials and Methods: In this cross sectional research, 240 subjects were selected. Sixty cases (30 girls and 30 boys) with normal occlusion within 16-18 years old were selected in random cluster sampling from high schools in Mashhad. Examination technique was direct observation, lateral cephalometric radiography, impression and preparing study model for measuring. For every kind of malocclusion 60 young patients, 30 females and 30 males, within the range of 16-20 years old attended orthodontic treatment in private dental offices or Orthodontics Department of Mashhad Dental School .The examination technique was indirect observation, using lateral cephalometry selected of 5395 lateral cephalograms and related study models for measuring. Mean, minimum, maximum. and height of the palate was initially determined and then normal occlusion was compared with every kind of malocclusion using SPSS statistical software. One way analysis of variance (ANOVA), t-test (independent groups) and also Duncan test were used for comparison. Results: The ANOVA test showed that there were no statistically significant differences between females in normal occlusion and different malocclusions (P=0.486). In boys the palatal height was significantly higher in class III males than class II and class I malocclusions and the height of palate for normal boys is significantly higher than class I malocclusion (P